Climate treaties and backstop technologies - Scott Barrett (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper I examine the design of climate treaties when there exist two kinds of technology, a conventional abatement technology with (linearly) increasing marginal costs and a backstop technology ('air capture') with high but constant marginal costs. I focus on situations in which countries can gain collectively by using both technologies. I show that, under some circumstances, countries will be better off negotiating treaties that are not cost-effective. When countries prefer to negotiate self-enforcing agreements that are cost-effective, the availability of the backstop technology causes cooperation in abatement to increase significantly.
Keywords: Q54; 330; Klimaschutz; Umweltabkommen; Anreizvertrag; Luftreinhaltung; Umwelttechnik; Umweltschutzkosten; Grenzkosten; Theorie